Dipeptidyl peptidase IV (DPIV/CD26) degradation of glucagon. Characterization of glucagon degradation products and DPIV-resistant analogs - Hinke, S A; Pospisilik, J A; Demuth, H U; Mannhart, S; Kühn-Wache, K; Hoffmann, T; Nishimura, E; Pederson, R A; McIntosh, C H (The Journal of biological chemistry, 2000)
Over the past decade, numerous studies have been targeted at defining structure-activity relationships of glucagon. Recently, we have found that glucagon(1-29) is hydrolyzed by dipeptidyl peptidase IV (DPIV) to produce glucagon(3-29) and glucagon(5-29); in human serum, [pyroglutamyl (pGlu)(3)]glucagon(3-29) is formed from glucagon(3-29), and this prevents further hydrolysis of glucagon by DPIV (H.-U. Demuth, K. Glund, U. Heiser, J. Pospisilik, S. Hinke, T. Hoffmann, F. Rosche, D. Schlenzig, M. Wermann, C. McIntosh, and R. Pederson, manuscript in preparation). In the current study, the biological activity of these peptides was examined in vitro. The amino-terminally truncated peptides all behaved as partial agonists in cyclic AMP stimulation assays, with Chinese hamster ovary K1 cells overexpressing the human glucagon receptor (potency: glucagon(1-29) > [pGlu(3)]glu- cagon(3-29) > glucagon(3-29) > glucagon(5-29) > [Glu(9)]glu- cagon(2-29)). In competition binding experiments, [pGlu(3)]glucagon(3-29) and glucagon(5-29) both demonstrated 5-fold lower affinity for the receptor than glucagon(1-29), whereas glucagon(3-29) exhibited 18-fold lower affinity. Of the peptides tested, only glucagon(5-29) showed antagonist activity, and this was weak compared with the classical glucagon antagonist, [Glu(9)]glucagon(2-29). Hence, DPIV hydrolysis of glucagon yields low affinity agonists of the glucagon receptor. As a corollary to evidence indicating that DPIV degrades glucagon (Demuth, et al., manuscript in preparation), DPIV-resistant analogs were synthesized. Matrix-assisted laser desorption/ionization-time of flight mass spectrometry was used to assess DPIV resistance, and it allowed kinetic analysis of degradation. Of several analogs generated, only [D-Ser(2)] and [Gly(2)]glucagon retained high affinity binding and biological potency, similar to native glucagon in vitro. [D-Ser(2)]Glucagon exhibited enhanced hyperglycemic activity in a bioassay, whereas [Gly(2)]glucagon was not completely resistant to DPIV degradation.